PUBLIC LIBRARIES OF JAFFNA DISTRICT: PROBLEMS AND CONSTRAINTS TOWARDS DEVELOPMENT - Chandrasekar, K.; Visakaruban, M. (Sri Lanka Library Association, 2005)
Establishment of Public libraries is regarded as one of the essential amenities of the local or central government of a nation since they enhance the idea of free and equal access to information and offers their collections and services to all members of the community. This study revealed the present status of the Public libraries in the Jaffna District. Apart from the Jaffna Public Library, which is managed by the Jaffna Municipal Council and provide services to the whole Jaffna District, presently there are 05 Urban Council libraries, 48 Pradeshiya Sabha libraries and 310 Community Center libraries, which cater the needs of the general public of the respective areas in the Jaffna District. Conflict situation which prevailed in the region, insufficient funding and inadequate infrastructure facilities, lack of interest and motivation from authorities, shortage of staff, lack of Library and Information Science (LIS) education, lack of in-service training programs for library staff and absence of Co-ordination or guidance for libraries at District level are the major constraints to these Public libraries in the Jaffna District. After signing the MOU between the Government of Sri Lanka and LTTE in 2002, many foreign and local Non Government organizations and United Nations agencies started to reconstruct and develop some of the public libraries of Jaffna District with the foreign funded projects. But still there is a need for training programmes (courses) for professionals and Para-professionals, in-service training for existing staff in the libraries, awareness programmes for public, and formation of consortia to co-ordinate the activities of the libraries in the Jaffna District.